A PROCESS-GENRE APPROACH TO TEACHING WRITING REPORT TEXT TO SENIOR HIGH SCHOOL STUDENTS - Pujianto, Dimas; Emilia, Emi; Ihrom, Sudarsono Muhammad (Universitas Pendidikan Indonesia, 2014)
Abstract: This study is aimed at exploring whether a process-genre approach (PGA) teaching steps can help develop senior high students’ writing skills of report text based on schematic structures and linguistic features analysis. A descriptive research design embracing case study characteristics was employed (Nunan, 1992; Cresswell, 2012). The data were gained from teaching process and students’ texts analysis. The basic framework of process-genre approach is the synthesis of teaching steps in genre- and process-based approaches (Badger White, 2000; Emilia, 2010). Students’ texts were analyzed in terms of Report text’s schematic structures and linguistic features using SFL GBA frameworks (Linguistic and Education Research Network, 1990; Gerot Wignell, 1994; Halliday, 1994; Anderson Anderson, 1997; Christie, 2005; Feez Joyce, 2006; Hyland 2007; Emilia, 2012). The results show that, to some extent, PGA helps students develop writing skills of Report text specifically on the genre knowledge, writing process, and feedback from peers and teacher which was observed from the teaching process and schematic structures and linguistic features analysis. Nevertheless, it is figured out that the low-achieving students need longer modelling and teacher-student conference stages. This study is expected to contribute towards teacher’s understanding in implementing and overcoming problems related to PGA in EFL classes in Indonesia, especially in emphasizing the modelling stage for the low-achieving students and in teaching other genres and language skills. Keywords: Process-based approach, genre-based approach, process-genre approach